THE ROLE OF THE UNITED NATIONS CHILDREN'S FUNDS (UNICEF) IN HANDLING ROHINGYA CHILDREN REFUGEES IN BANGLADESH 2016-2018 - Anne F. Damanik (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Currently, there are still many countries that are still living closely together with conflicts that have not been resolved day by day. The world is still mourning the many conflicts that occur due to political, economic, socio-cultural problems and ethnic, religious and racial differences.The United Nations Children's Fund (UNICEF) is an organization formed by the United Nations (UN) under the UN General Assembly. The UN has a system known as "The United Nations Family", consisting of the UN itself which is the parent organization and within which there are many funding programs and affiliated special institutions. UNICEF carries out its duties in protecting the rights of Rohingya children working on the basis of cooperation with the Government of Bangladesh. Through the existing division of labor, UNICEF's role is as an instrument to collect and distribute aid funds coming from various circles in the world to Rohingya children in Bangladesh as well as providing information and fundraising promotions for Rohingya refugee children in Bangladesh. UNICEF established its first office in Bangkok with responsibility for East Pakistan. Then in 1950 UNICEF opened its first office in Dhaka with two professional staff and a driver. Since then UNICEF has started collaborating with the Health Secretariat for tuberculosis (smallpox), smallpox, malaria and cholera. This collaboration serves to develop maternal and child health services as well as training for better health service provision in Bangladesh. This program includes the provision of latrines, increasing the supply of clean water and support for various initiative activities in the areas of education, training and livelihood development. And this program ended in 1970.